Evaluating the Relationship Between Meander‐Bend Curvature, Sediment Supply, and Migration Rates. Issue 3 (26th March 2021) - Donovan, Mitchell; Belmont, Patrick; Sylvester, Zoltán
Abstract: River meander migration plays a key role in the unsteady "conveyor belt" of sediment redistribution from source to sink areas. The ubiquity of river meandering is evident from remotely sensed imagery, which has allowed for long‐term, high‐resolution studies of river channel change and form‐process relationships. Empirical, experimental, and theoretical research approaches have described two distinct relationships between channel curvature and river channel migration rates. In this study, we employ a novel application of time‐series algorithms to calculate migration rates and channel curvature at sub‐meander bend length scales using 6 decades of aerial imagery spanning 205 km of the Minnesota River and Root River, Minnesota, USA. Results from the Minnesota River provide the first empirical evidence demonstrating how migration‐curvature relations break down for rivers with low sediment supply, which is supported by the Root River data set. This not only highlights the importance of sediment supply as a driver of river migration, but also supports a simple means to detect river reaches lacking sediment supply. Furthermore, results from both rivers demonstrate that sub‐meander bend measurement scales are most appropriate for studying channel migration rates and further indicate that a quasi‐linear relationship—rather than the more commonly inferred peaked relationship—exists between channel curvature and migration rates. The highest migration rates are associated with the highest measured channel curvatures in our data set, after accounting for a spatial lag of 2.5 ± 0.2 0.3 channel widths. These findings are consistent with flume experiments and empirical data across diverse geologic and climatic environments. Plain Language Summary: River meander migration plays a key role in the redistribution of sediment from uplands and headwaters to valley bottoms, lakes, reservoirs and the ocean. In this study, we measure both river migration rates and curvature at high resolution (every 10‐m) using six‐decades of aerial imagery spanning 205 river‐km of the Minnesota and Root rivers, Minnesota, USA. Our results demonstrate how differences in measurement scales led to different interpretations in previous research, and that high‐resolution measurements are most useful for understanding curvature‐migration relationships. The highest migration rates are associated with the highest measured channel curvatures, after accounting for a spatial lag of 2.5 ± 0.25 channel widths. These findings are consistent with flume experiments and empirical data across diverse geologic and climatic environments. Lastly, we demonstrate that curvature‐migration relations cease for rivers with low sediment supply. This finding highlights the importance of sediment supply as a driver of river migration and establishes a simple means of detecting river reaches lacking bedload sediment transport. Key Points: Migration rates are negligible and migration‐curvature relations break down along reaches with low sediment supply Curvature‐migration relationships consistently peak at lag distances of ∼2.5 ± 0.25 channel‐widths regardless of climate and geology Results support empirical, flume, and theoretical findings of a direct monotonic relation between channel curvature and migration rates